Minimum 5-Year Follow-up on Graduates of Growing Spine Surgery for Early Onset Scoliosis. Issue 10 (November 2020) - Murphy, Robert F.; Barfield, William R.; Emans, John B.; Akbarnia, Behrooz; Thompson, George; Sponseller, Paul; Skaggs, David; Marks, David; Smith, John T.; Flynn, John; Presson, Angela; Sawyer, Jeffrey R.; et al.
Abstract : Introduction: After discontinuation of growth friendly (GF) surgery for early onset scoliosis, patients undergo spinal fusion or continued observation. This last planned treatment is colloquially called "definitive" treatment, conferring these patients as "graduates" of a growing program. The 5-year radiographic and clinical outcomes of this cohort are unknown. Methods: An international pediatric spine database was queried for patients from a GF program (spine or rib-based) with minimum 5-year follow-up from last planned surgery (GF or spinal fusion). Radiographs and charts were reviewed for main coronal curve angle and maximum kyphosis as well as occurrence of secondary surgery. Results: Of 580 graduates, 170 (29%) had minimum 5-year follow-up (37% male). Scoliosis etiology was congenital in 41 (24%), idiopathic 36 (21%), neuromuscular 51 (30%), and syndromic 42 (25%). Index surgery consisted of spine-based growing rods in 122 (71%) and rib-based distraction in 48 (29%). Mean age at index surgery was 6.8 years, and patients underwent an average of 5.4 lengthenings over an average of 4.9 years (range, 6 mo to 11 y). Last planned treatment was at an average age of 11.8 years (range, 7 to 17 years). Last planned treatment consisted of spinal fusion in 114 patients, 47 had growing implants maintained, 9 had implants removed. Average follow-up was 7.3 years (range, 5 to 13 y). When compared from postdefinitive treatment to 2-year follow-up, there was noted progression of the coronal curve angle (46±19 to 51±21 degrees, P =0.046) and kyphosis (48±20 to 57±25 degrees, P =0.03). However, between 2 and 5 years, no further progression occurred in the coronal (51±21 to 53±21 degrees, P =0.26) or sagittal (57±25 to 54±28 degrees, P =0.93) planes. When stratified based on etiology, there was no significant coronal curve progression between 2- and 5-year follow-up. When comparing spinal fusion patients to those who had maintenance of their growing construct, there was also no significant curve progression. Thirty-seven (21%) underwent at least 1 (average, 1.7; range, 1 to 7) revision surgery following graduation, and 15 of 37 (41%) underwent 2 or more revision surgeries. Reason for revision was implant revision (either GF or spinal fusion) in 34 patients, and implant removal in 3. On an average, the first revision was 2.5 years after the definitive treatment plan (range, 0.02 to 7.4 y). In total, 15 of 37 (41%) revisions occurred over 2 years following the final decision for treatment plan, and 7 of 37 (19%) occurred 5 or more years after the definitive treatment. Patients who underwent spinal fusion as a definitive treatment strategy were more likely to undergo revision surgery (27%) than patients who had their GF implants maintained (11%) ( P =0.04). Conclusions: Five years following "graduation" from growing surgery for early onset scoliosis, there is progression of curve magnitude in both the coronal and sagittal planes up to 2 years, with no further progression at 5 years. A total of 21% of patients undergo at least 1 revision surgery, and average time to revision surgery is over 2 years from last planned surgery. Risk of revision surgery was higher in patients who underwent a spinal fusion as their definitive treatment strategy. Level Evidence: Level III—retrospective comparative. Type of Evidence: Therapeutic.